Political euphemization in the news article headlines - Smetonienė, Irena; Daučiūnaitė, Danutė (Kalbotyra, 2016)
The article is devoted to the analysis of realizations of euphemization in political discourse. Its focus is on news article headlines. The language data under study have been collected from the Internet news websites published in 2013–2014. The aim of the paper is twofold: to give an overview of recent cases of euphemization in news headlines, and to define functions, purpose and means of euphemization. The most frequently euphemized topics this year have been found to be war, military actions in different countries, politics and economics. The analysis of the news article headlines has showed that one of the main purposes of euphemization of social problems and political issues is to veil and cover up the real names of such phenomena as military actions, massacre, preparation for war, rising prices, unsuitable behavior of various officials, conflicts between leading politicians, bad economic conditions. The sub-topics of euphemization are concerned with the criticism of the behaviour of government leaders, leading politicians who are claimed to have violated ethics, who are arrogant, corrupt and dishonest. The semantics of euphemisms is best reflected describing them according to the means of euphemization, which are generalization, conceptual metaphorization, choice of international terms, periphrasis, pronominalization and litotes. Political euphemisms are part and parcel of the world of diplomacy, international and internal policy; politically correct language is crucial in today’s mass media communication. It seeks to avoid conflict and antagonism, reduce panic and anxiety, and to disguise unpleasant news.